Profil Berpikir Metaforis Siswa SMP Dalam Memecahkan Masalah Matematika Ditinjau Dari Gaya Kognitif - Arni, Nanda Cintya (Universitas Dr. Soetomo, 2019)
Abstract This research is a descriptive research using qualitative approach. This research is aimed to describe metaphorical thinking profile in solving algebra problem based on students’ cognitivity. In conducting this research , two students were being the subject pf the study. First student was using cognitive field-indepedent and another student using field-dependent. The data were collected by conducting writing test and interviewing. Furthermore, analyzing was conducted base on indicator of metaphorical thinking phases that illustrated with CREATE. The finding revealed that the subject that used cognitive field-independent was able to make metaphor in connect phase, in relate phase the subject was able to explain mathematical concept that was used to solve the given problem. In explore phase, the subject was able to make her own mathematical model from the problem. In analyze phase, the subject could explain operation steps from the previous model. In transform phase, the subject was able to solve algebra problem correctly. Last, in experience phase, the subject could make algebra problem. The subject with cognitive field-dependent was able to make metaphor in connect phase. But, the subject could not make to next relate and explore phases. In transform phase, the subject was able to interpret algebra problem without using mathematical model operational process but using metaphor concept that he had made before. In experience phase, the subject could make algebra. Keywords: Metaphorical Thinking, Problem Solving, Cognitive Style Abstrak Penelitian ini merupakan penelitian deskriptif dengan pendekatan kualitatif. Penelitian ini bertujuan untuk mendeskripsikan profil berpikir metaforis dalam memecahkan masalah aljabar ditinjau dari gaya kognitif. Penelitian ini memiliki dua subjek yang terdiri atas subjek dengan gaya kognitif field-independent dan field-dependent. Pengumpulan data dilakukan dengan tes tulis dan wawancara, kemudian dianalisis berdasarkan indikator pada tahap-tahap berpikir metaforis yang digambarkan dengan CREATE (Connect, Relate, Explore, Analyze, Transform dan Experience). Hasil penelitian menunjukan bahwa subjek dengan gaya kognitif FI pada tahap Connect mampu membuat perumpamaan metafora, tahap Relate mampu menjelaskan konsep matematika yang digunakan untuk menyelesaikan masalah yang disajikan, tahap Explore subjek mampu membuat model matematika dari permasalahan. Pada tahap Analyze subjek mampu menjelaskan setiap langkah operasi dari model matematika yang telah dibuat. Tahap Transform subjek mampu menafsirkan jawaban aljabar yang didapat secara tepat. Dan pada tahap experience subjek mampu membuat permasalahan aljabar baru. Subjek dengan gaya kognitif FD mampu membuat perumpamaan metafora pada tahap Connect. Tapi, subjek tidak dapat mengungkap tahap Relate dan Explore. Pada tahap Transform subjek mampu menafsirkan hasil akhir dari permasalahan aljabar yang didapat walaupun tanpa melalui proses operasional model matematika melainkan dari metafora yang telah dibuat. Pada tahap Experience subjek mampu membuat permasalahan aljabar baru berdasarkan model permasalahan sebelumnya. Keywords: BerpikirMetaforis, Pemecahan Masalah, Gaya Kognitif